15.6.Ex14-15

15.6.Ex14-15 - = ( , 1 ) : x = e cos 1 = cos 1 , y = e sin...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
SECTION 15.6 The Chain Rule (ET Section 14.6) 711 14. g s at s = 4, where g ( x , y ) = x 2 y 2 , x = s 2 + 1, y = 1 2 s . SOLUTION We fnd the primary derivatives oF g ( x , y ) = x 2 y 2 : g x = 2 x , g y =− 2 y Applying the Chain Rule gives g s = g x · dx ds + g y · dy ds = 2 x dx ds 2 y dy ds (1) We compute dx ds and dy ds : dx ds = 2 s , dy ds =− 2 Substituting in (1) we obtain g s = 4 xs + 4 y (2) We now determine ( x , y ) For s = 4: x = 4 2 + 1 = 17 , y = 1 2 · 4 =− 7 Substituting ( x , y ) = ( 17 , 7 ) and s = 4 in (2) gives the Following derivative: g s ¯ ¯ ¯ ¯ s = 4 = 4 · 17 · 4 4 · 7 = 244 15. g u at ( u ,v) = ( 0 , 1 ) ,where g ( x , y ) = x 2 y 2 , x = e u cos v , y = e u sin v . SOLUTION The primary derivatives oF g ( x , y ) = x 2 y 2 are g x = 2 x , g y =− 2 y By the Chain Rule we have g u = g x · x u + g y · y u = 2 x x u 2 y y u (1) We fnd x u and y u : x u = e u cos v, y u = e u sin v Substituting in (1) gives g u = 2 xe u cos v 2 ye u sin v = 2 e u ( x cos v y sin v) (2) We determine ( x , y ) For ( u ,v)
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = ( , 1 ) : x = e cos 1 = cos 1 , y = e sin 1 = sin 1 inally, we substitute ( u , v) = ( , 1 ) and ( x , y ) = ( cos 1 , sin 1 ) in (2) and use the identity cos 2 sin 2 = cos 2 , to obtain the Following derivative: g u ( u ,v) = ( , 1 ) = 2 e cos 2 1 sin 2 1 = 2 cos 2 1 = 2 cos 2 16. h q at ( q , r ) = ( 3 , 2 ) , where h ( u , v) = ue v , u = q 3 , v = qr 2 . SOLUTION We frst fnd the primary derivatives oF h ( u , v) = ue v : h u = e v , h v = ue v...
View Full Document

This note was uploaded on 02/13/2010 for the course MATH MATH 32A taught by Professor Park during the Fall '09 term at UCLA.

Ask a homework question - tutors are online